Avaliação do conhecimento da equipe de enfermagem sobre doença periodontal e suas associações com alterações sistêmicas - Elisangela, Rodrigues (2023)
The aim of this study was to assess the knowledge of the nursing staff working at hospital units about periodontal disease and its association with systemic diseases, as well as the clinical management of patients with periodontal disease. A cross-sectional observational study was carried out with 504 nursing professionals who completed a self-administered questionnaire with 24 objective questions related to the knowledge of nurses and nursing staff regarding oral care procedures and the importance of oral health in hospitalized patients with periodontal disease. Data were analyzed where descriptive and the chi-square test were performed, considering a significance value of 5%. The majority of respondents (97.8%) believe that oral infection can affect the patient's general health and that oral hygiene is important during hospitalization. However, knowledge about the effects of periodontal disease in the oral cavity was considered moderate by 49.3% of the participants, and 74.6% believe that sugar is the most common causal factor for periodontal disease. Professionals know the importance of maintaining patient oral hygiene and the relationship of periodontal disease with systemic diseases, but practical knowledge seems to be deficient. A training program on oral health care of inpatients and the inclusion of oral hygiene topics in the curriculum of nursing professionals is suggested.